Design of a Mobile-Based Waste Management Application with a Waste Identification Feature as a Public Education Medium - Dandy Cahyo Purnomo; Ahmad Hasib Satiri; Eka Aprilia Saputri; Luluk Khatimah; Hartono (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2026)
The waste problem in Indonesia requires technological solutions to raise public awareness. This study aims to design a mobile-based waste management application as a medium for public hygiene education. Using engineering methods, it has four main features: waste type identification through camera scans, waste disposal management, digital waste management literacy, and a recycled product marketplace. The design stages include system specification analysis, interface design, and functionality testing. System testing results using the System Usability Scale (SUS) method involving 10 respondents showed an average score of 76.7. Based on SUS assessment standards, this score falls into the "Acceptable" category with an Adjective Rating of "Good" . This demonstrates that the waste identification feature makes it easier for users to recognize and sort waste independently, and all system functions perform according to design specifications. This application is expected to be an effective digital instrument in increasing environmental awareness and community independence in managing household waste.